In Vitro Evolution Reveals Noncationic Protein-RNA Interaction Mediated by Metal Ions - Giacobelli, Valerio G; Fujishima, Kosuke; Lepšík, Martin; Tretyachenko, Vyacheslav; Kadavá, Tereza; Makarov, Mikhail; Bednárová, Lucie; Novák, Petr; Hlouchová, Klára (Molecular biology and evolution, 2022)
RNA-peptide/protein interactions have been of utmost importance to life since its earliest forms, reaching even before the last universal common ancestor (LUCA). However, the ancient molecular mechanisms behind this key biological interaction remain enigmatic because extant RNA-protein interactions rely heavily on positively charged and aromatic amino acids that were absent (or heavily under-represented) in the early pre-LUCA evolutionary period. Here, an RNA-binding variant of the ribosomal uL11 C-terminal domain was selected from an approximately 1010 library of partially randomized sequences, all composed of ten prebiotically plausible canonical amino acids. The selected variant binds to the cognate RNA with a similar overall affinity although it is less structured in the unbound form than the wild-type protein domain. The variant complex association and dissociation are both slower than for the wild-type, implying different mechanistic processes involved. The profile of the wild-type and mutant complex stabilities along with molecular dynamics simulations uncovers qualitative differences in the interaction modes. In the absence of positively charged and aromatic residues, the mutant uL11 domain uses ion bridging (K+/Mg2+) interactions between the RNA sugar-phosphate backbone and glutamic acid residues as an alternative source of stabilization. This study presents experimental support to provide a new perspective on how early protein-RNA interactions evolved, where the lack of aromatic/basic residues may have been compensated by acidic residues plus metal ions.
Keywords: protein evolution; ionty; Molecular Dynamics Simulation; Ions; Amino Acids; simulace molekulární dynamiky; genetic code evolution; aminokyseliny; RNA–protein interaction; mRNA-display; RNA